The underlying structure of the Personality Inventory for DSM-5 (PID-5): a general factor of personality psychopathology - Silvana A. Montes; Roberto O. Sanchez (Current Issues in Personality Psychology, 2023)
Background The psychopathology of personality is currently undergoing a paradigm shift from a categorical to a dimensional approach. This work aimed to study the underlying structure of pathological personality traits of the DSM-5 Alternative Model for Personality Disorders (AMPD). For this purpose, the internal structure of a version of the Personality Inventory for the DSM-5 (PID-5) was examined by a confirmatory factor analysis. This version assesses the five higher-order pathological personality domains (negative affectivity, detachment, antagonism, disinhibition, and psychoticism) and the 25 lower-order pathological personality facets through a reduced number of items. Four alternative models were compared: five-factor oblique; second-order (five first-order factors and one second-order factor); bifactor (five specific factors and a general fac-tor), and one-factor.